A variável (R) em coda silábica medial no Bairro Várzea, em Lagoa Santa/MG - Maria Helena Soares Paes (2014)
This research, based on the Theory of Linguistic Variation and Change, Labov (1972), aim sat identifying and analyzing the occurrences of the (R) variable in medial syllabic coda, in Várzea district, in Lagoa Santa city, Minas Gerais, Brazil. The retroflex variant of (R), that shares the same environment with the glottal fricative, was the starting point of this study. However, while we were making the data analysis, other variants appeared, so we have analyzed them too. We noticed that the retroflex variant of (R) was performed by adults only. We have found evidences that the fricative variant has been in progression in the studied community.